Ketahanan Keluarga pada Rumah Tangga Tenaga Kerja Indonesia ( TKI ) : Studi Kasus Masyarakat Desa Tlogopucang Kec. Kandangan Kab. Temanggung - M Fahmi Qismatuttoyibbin (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Marriage is an important moment in the life cycle of a human being. Essentially, marriage unites two individuals from different backgrounds within the same group to achieve common goals and to love and care for each other. This study aims to: (1) Examine family resilience when the husband or wife works abroad in Tlogopucang Village, Kandangan Sub-district, Temanggung Regency in 2024. (2) Identify the factors that strengthen family resilience when the husband or wife works abroad (a case study in Tlogopucang Village, Kandangan Sub-district, Temanggung Regency in 2024).The researcher used field research with a qualitative descriptive approach. The respondents included four individuals working abroad and two members of the community in Tlogopucang Village, Kandangan Sub-district, Temanggung Regency. Data collection was carried out through observation, interviews, and documentation. The data were then analyzed through continuous observation and interviews.The findings of the study are as follows: (1) The family resilience of husbands or wives working abroad (in Tlogopucang Village, Kandangan Sub-district, Temanggung Regency in 2024) involves four migrant workers (TKI) working abroad. Most of these workers prioritize maintaining their families rather than resorting to divorce. (2) The factors that strengthen family resilience for husbands or wives working abroad (in Tlogopucang Village, Kandangan Sub-district, Temanggung Regency in 2024) include effective communication, providing clear updates, and mutual trust between husband and wife. These factors serve as a foundation for maintaining a long-distance relationship. Additionally, family support in Tlogopucang Village is not solely derived from within the family but also from the surrounding community, including parents, society, and religious leaders.